A genetic screen identifies new regulators of steroid-triggered programmed cell death in Drosophila. - Wang, L.; Evans, J.; Andrews, H.K.; Beckstead, R.B.; Thummel, C.S.; Bashirullah, A. (Genetics, 2008)
The steroid hormone ecdysone triggers the rapid and massive destruction of larval tissues through transcriptional cascades that culminate in rpr and hid expression and caspase activation. Here we describe the use of genetic screens to further our understanding of this steroid-triggered programmed cell death response. Pupal lethal mutants were screened for specific defects in larval salivary gland destruction. A pilot screen using existing P-element collections resulted in the identification of mutations in known cell death regulators, E74 and hid, as well as multiple alleles in CBP (nejire) and dTrf2. A large-scale EMS mutagenesis screen on the third chromosome resulted in the recovery of 48 mutants. These include seven multiallelic complementation groups, at least five of which do not map to regions or genes previously associated with cell death. Five mutants display defects in the transcriptional induction of rpr and hid, and all display a penetrant block in caspase activation. Three were mapped to specific genes: CG5146, which encodes a protein of unknown function, Med24, which encodes a component of the RNA polymerase II mediator complex, and CG7998, which encodes a putative mitochondrial malate dehydrogenase. These genetic screens provide new directions for understanding the regulation of programmed cell death during development.